2010
DOI: 10.1590/s1808-18512010000200013
|View full text |Cite
|
Sign up to set email alerts
|

Clasificación de las fracturas toracolumbares: comparación entre las clasificaciones de AO y Vaccaro

Abstract: OBJETIVO: as classificações têm mudado na último metade do século, sendo a mais usada desde a última década, a classificação AO. Em 2004, Vaccaro et al. propuseram a Thoraco-Lumbar Injury Classification (TLICS). MÉTODOS: análise da reprodução inter e intraobservador, utilizando o teste Kappa das classificações entre três níveis distintos de traumatólogos em formação, em 30 casos. RESULTADOS: a reprodução intraobservador na classificação de Vaccaro foi: OI: 0,73; OII: 0,6 e OIII: 0,63. Para a classificação AO, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0
5

Year Published

2013
2013
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 9 publications
0
6
0
5
Order By: Relevance
“…3,13,14 There has always been a difficulty between using simpler systems that end up omitting some information and more complex systems that cause a lot of disagreement among professionals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3,13,14 There has always been a difficulty between using simpler systems that end up omitting some information and more complex systems that cause a lot of disagreement among professionals.…”
Section: Discussionmentioning
confidence: 99%
“…Bazán et al 14 compared the AO/Magerl 1994 and TLICS classifications and demonstrated the favorability of the latter because it is easier for physicians familiar with spine and spinal cord lesions to interpret. They used the Kappa index for statistical analysis.…”
mentioning
confidence: 99%
“…Several studies 34,35 were conducted to define the reproducibility of cervical and thoracolumbar fracture classifications. Most neurosurgeons use only the AO method, while orthopedists tend to complement it with other classifications such as the Denis, Harms, SLICS, TLICS, and especially Allen-Ferguson.…”
Section: Discussionmentioning
confidence: 99%
“…1,3,6,7 Over time several spine fracture classification systems have been developed, dating from 1929 up to the most recent one established by the AO System, based on morphopathological criteria according to the mechanism of injury and the degree of instability and establishing prognostic considerations in relation to recovery potential. 3,5,[7][8][9][10][11] In addition to the AO classification for thoracolumbar spine fractures, two scoring scales are used to determine the degree of severity of the thoracolumbar injury and to make decisions about how to handle it: the first, presented by Vaccaro et al in 2005, the Thoracolumbar Injury Severity Score (TLISS), and the second, presented in 2013 by the collaborators of AOSpine, the Thoracolumbar AOSpine Injury Score (TL AOSIS). In both scales, conservative management is ruled out for scores greater than 5 points.…”
Section: Introductionmentioning
confidence: 99%
“…In both scales, conservative management is ruled out for scores greater than 5 points. 3,5,[7][8][9][10] Burst fractures of the thoracolumbar spine have an incidence of neurological deficit of up to 14% and are present to a great extent in the daily routine of the Orthopedic and Traumatology Services. [12][13][14][15] At present, there are two viable treatment options for this pathology: conservative treatment and surgical management, but there is still a lack of information in the Clinical Practice Guides to help us choose between the two management options.…”
Section: Introductionmentioning
confidence: 99%